Efficient, environment friendly and regioselective synthetic strategy for 2/3-substituted-8,8-dimethyl-8,9-dihydropyrazolo[1,5-a]quinazolin-6(7H)-ones and their structure elucidation - Das, Susma; Marpna, Labet Bankynmaw; Vishwakarma, Jai Narain (European Journal of Chemistry, 2022)
An efficient and regioselective synthetic reaction friendly to the environment has been described to synthesize various derivatives of pyrazolo[1,5-a]quinozolinone. Condensation of aminopyrazole (4a-m) with formylated dimedone (3) in the presence of KHSO4, under ultrasonic irradiation furnished 2/3-substituted 8,8-dimethyl-8,9-dihydropyrazolo[1,5-a]quinazolin-6(7H)-one (6a-m). This is a clean reaction, giving excellent yields with short reaction time. The structures were elucidated with the help of spectral and analytical data. X-ray crystallographic studies of a model compound 6a ascertained its structural configuration, crystal data for C12H12BrN3O (M =294.152 g/mol): Triclinic, space group P-1 (no. 2), a = 5.872(4) Å, b = 10.870(8) Å, c = 19.523(15) Å, α = 90.013(10)°, β = 90.009(11)°, γ = 93.838(11)°, V = 1243.3(16) Å3, Z = 4, T = 296.15 K, μ(Mo Kα) = 3.293 mm-1, Dcalc = 1.571 g/cm3, 37271 reflections measured (4.18° ≤ 2Θ ≤ 52.7°), 5073 unique (Rint = 0.2404, Rsigma = 0.2366) which were used in all calculations. The final R1 was 0.0596 (I≥2σ(I)) and wR2 was 0.1759 (all data).